Leadership behaviours and practices assessment among nurse managers in riyadh second health cluster - Salman Mohammed Alharbi; Ahmed Mansour Almansour (BMC Nursing)
Abstract Background The leadership behaviours and practices of nurse managers play a pivotal role in shaping staff performance, retention, and the overall quality of patient care, making them critical components of healthcare system efficiency and outcomes. These behaviours and practices are attributed to different management strategies and leadership styles, which have a strong influence on how leaders act and make decisions. Aim This study aims to assess the leadership behaviours and practices of nurse managers within Riyadh Second Health Cluster. Methodology A cross-sectional quantitative study was conducted using the Leadership Practices Inventory (LPI), a validated 30-item self-assessment tool. A total of 342 nurse managers working in Riyadh Second Health were recruited using convenience sampling. Data were analyzed using descriptive statistics, independent t-tests, and ANOVA to examine differences across their demographics. Results Significant differences were found in leadership behavior scores across gender, nationality, age, education, and experience, with female, non-Saudi, mid-career, and bachelor’s-prepared nurse managers demonstrating higher self-reported leadership practices across all domains. Nurse managers exhibited very high leadership scores across all five domains of the leadership practices (average M = 4.57); Model the Way (M = 4.57), Inspire a Shared Vision (M = 4.56), Challenge the Process (M = 4.56), Enable Others to Act (M = 4.57), and Encourage the Heart (M = 4.57). Conclusion The results indicated a very high level of all leadership practices among the nurse managers in Riyadh Second Health Cluster. The study findings highlight a strong leadership abilities among the nurse managers, emphasizing the need for continued investment in leadership training and development programs to enhance staff performance, retention, and quality of care.